The Concept of Police Discretion Against Children in Conflict with the Law - Susilo, Agus (UNISSULA Semarang, 2025)
The purpose of this research is toto study and analyze the form of police discretion in dealing with children in conflict with the law. In this writing, the author uses a normative legal method with research specifications in the form of descriptive analysis. Investigation of a child by the police is a measure of the child's personality, he can be good or otherwise, therefore a special police unit is needed that is trained in serving and handling children. Discretion as one way to handle child cases is one of the authorities of the police in using their discretionary authority. Discretion is expected to minimize the number of children who must experience detention and all forms of rules in positive criminal law or create children as victims of criminal behavior of children. In the Child Criminal Justice System Law, discretion is given to investigators to be able to seek diversion. This can be seen in Article 29 of the Child Criminal Justice System Law, namely: Investigators are required to seek diversion no later than 7 days after the investigation begins; The diversion process as referred to in paragraph 1 is carried out no later than 30 days after the start of the diversion.